The Indicators Of Village Administrative Officers Understanding Of Siskeudes: A Literature Study - Pawiro, Yulianti; Janie, Dyah N. A. (Economics and Business Solutions Journal, 2017)
This research is grounded by the enforcement of Village Law and disbursement of Village Fund. The substantial amount of Village Fund demands a more complex accountability. The limited time and inadequate human resources available, this village fund is susceptible to leakage which may be caused by either errors or irregularities.Using literature study method, this research attempts to explore the factors potentially related to village administrative governance and understanding of Village Financial System or Sistem Keuangan Desa (Siskeudes).The results indicate that there are five resultant variables, namely: understanding of Siskeudes, village financial management principles, special fund distribution or Village Fund Allocation (Alokasi Dana Desa/ADD), village financial administration, village financial reporting and accountability and understanding of village-owned property report. This research still needs to be developed further to test the validity of each variable generated in this research.